FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KETUBAN PECAH DINI (KPD) DI RS PKU MUHAMMADIYAH GAMPING - Kurrotul Ain Putri; Andri Nur Sholihah; Nidatul Khofiyah (Bajang Institute, 2025)
Premature Rupture of Membranes (PROM) is a pregnancy complication that can increase the risk of maternal and infant morbidity and mortality. PROM can occur before term gestation and is often associated with various risk factors, both internal and external. This study aims to determine the factors associated with the incidence of PROM at PKU Muhammadiyah Gamping Hospital. This research method is a quantitative study with a research design used is observational analytic correlation using a case control approach. The population in this study was 1052 mothers giving birth at PKU Muhammadiyah Gamping Hospital with a sample of 176 respondents consisting of 88 PROM cases and 88 controls, taken using quota sampling from medical record data for the period January 2023 - December 2024. Data were analyzed using the Chi-square test with a significance level of 0.05. The results showed that there was a significant relationship between parity (p = 0.000; OR = 4.002) and occupation (p = 0.000; OR = 3.765) with the incidence of PROM. Mothers with parity 1 or more than 4 times have a 4 times greater chance of experiencing PROM compared to parity 2–4. Likewise, mothers who work have a 3.7 times greater chance of experiencing PROM than those who do not work. Meanwhile, maternal age (p=0.853; OR=1.071) and pregnancy spacing (p=0.362; OR=1.521) did not show a significant relationship with the incidence of PROM. Conclusion: parity and employment factors are risk factors associated with the incidence of PROM at PKU Muhammadiyah Gamping Hospital. Special education, early detection, and monitoring efforts are needed for pregnant women with extreme parity and risky employment status in antenatal services at health facilities